Shared vision and network leadership in regional development case: the Lahti region in Finland - Vesa Kalevi Harmaakorpi; Harri Petteri Niukkanen (European Regional Science Association (ERSA), 2002)
The shift of techno-economic paradigm and European unification have radically changed the development environment of European regions. The regions are part of the worldwide network competing of essential flows to enable economic wellbeing. In the information era the regions in Finland have converted into subjects of regional development whereas in the industrial era they were largely objects of the nation-led regional policies. Regional development is nowadays a combination of manifold regional programs and strategies. Old-fashioned hierarchical methods do not seem to function in the new environment. New network-like of principals are needed in the regional development. The regions are developed in an environment, where regional actors and coalitions have their own visions and ways of acting. Regional development is a game, in which actors with different visions and strategies play together. Even though a regional development network is a relatively loose combination and cannot be compared with 'normal' organisations, the actors of the network should at least, on some level, things like -understanding of the reigning techno-economic and socio-institutional paradigms -shared vision of substance areas to be developed -shared opinion of development methods and evaluation of the development. The adaptation for information society in Lahti Urban Region has been quite painful and the region can be considered as a declined industrial region. A question often raised in the region is: Are the attitudes, visions, aims etc. of the regional actors coherent enough in order to enable the use of strong development activities in the region? The present research strives to assess the level of shared vision and commonly accepted ways of acting in Lahti Urban Region. The main reasons for declination in Lahti Urban Region are proposed to be the minute share of highly educated people and the low level in R&D spending, both facts that have caused a great deal of worry in the region. Therefore a special focus in the study was given to one development project generally thought as important for the successful development in Lahti Urban Region: 'Development of the high level education services and science park concept'. Special attention is given to how the actors of the region saw a regional network project, which has no separately specified host organisation. The empirical study was conducted by sending a questionnaire to 360 politicians, authorities, employees of regional development organisations, employees of regional education and research organisations and entrepreneurs in Lahti Urban Region. 155 questionnaires were returned making the response rate 43%. The main results of the study were following: -the respondents had noticed the new demands of the information society -the respondents thought the ways of acting in the region were not at all compatible with the new paradigm -other respondents except politicians formed a quite homogenous group in many ways -the opinion of funding the regional development was not at all unanimous -although development of higher education and R&D activities was seen important, only minority of the respondents knew about the studied project and were committed to the project.
Keywords: 330